Plukenetia volubilis L.: A New Record of a Cultivated Alien Species in Java - Tianara, Alexander; Handayani, Windri; Irsyam, Arifin Surya Dwipa; Hariri, Muhammad Rifqi; Dewi, Asih Perwita; Peniwidiyanti, Peniwidiyanti; Baidlowi, Muhammad Hisyam; Rosleine, Dian; Atria, Mega (Universitas Gadjah Mada, 2024)
Plukenetia volubilis L. has been documented as a new record for the first time in Java, Indonesia. The species is easily distinguished from the native species, P. corniculata Sm., by its exstipellate basilaminar-glands, long cylindrical column, and wingless fruit-lobes. Plukenetia volubilis is cultivated mainly in South America for its beneficial values as food and medicine and was recently introduced to Asia. However, its occurrence in Java has not been reported. We collected specimens from West Java (Depok City, Bandung Barat and Sumedang Regency) and East Java (Malang Regency). Morphological description, identification key, and photographs of the species are provided.